Revisão taxonômica de Schizolecis Britski & Garavello, 1984: (Loricariidae: Hypoptopomatinae) - Kusma, Camila Munareto (Pontifícia Universidade Católica do Rio Grande do Sul, 2013)
Made available in DSpace on 2013-08-07T19:12:34Z (GMT). No. of bitstreams: 1 000448697-Texto+Completo-0.pdf: 1821163 bytes, checksum: 8ebb362c20f003840cd87e504cc220af (MD5) Previous issue date: 2013 === The genus monotypical Schizolecis was proposed by Britski & Garavello (1984), being Microlepidogaster guntheri Miranda Ribeiro, 1918 the type species. Its distribution occurs from the north of the state of Santa Catarina until the north of the state of Rio de Janeiro, Brazil, comprising several coastal river basins. Due to the act that the genus is widely distributed in such isolated river basins, it was suggested the possibility of more than one species being included in what today we know as Schizolecis guntheri. To test this hypothesis, the following morphometric analysis were performed: tradition biometry and comparision of the interval of proportions; multivariate analyses of Principal Components and Canonical Variables and multivariate analyses of geometric morphometry using Relative Warps. Perceptible differences were not found among the individuals of the populations analyzed of Schizolecis guntheri, being only detected a gender dimorphism among the samples from Baía da Ilha Grande, in the state of Rio de Janeiro. A taxonomic revision was performed, together with a redescription of the genus and species. According to the results, it is concluded that all populations in differents coastal river basins of the state of Santa Catarina until the state of Rio de Janeiro, are a single species Schizolecis guntheri. === O gênero monotípico Schizolecis foi proposto por Britski & Garavello (1984), com Microlepidogaster guntheri Miranda Ribeiro, 1918 a espécie-tipo. Sua distribuição ocorre do norte do estado de Santa Catarina até o norte do estado do Rio de Janeiro, Brasil, compreendendo diversas bacias hidrográficas costeiras. Devido ao fato do gênero estar amplamente distribuído em bacias hidrográficas isoladas, sugeriu-se que haveria a possibilidade de mais de uma espécie estar incluída no que hoje conhecemos como Schizolecis guntheri. Para testar essa hipótese, foram realizadas as seguintes análises morfométricas: biometria tradicional e comparação de intervalo de proporções; análises multivariadas de Componentes Principais e Variáveis Canônicas e análises multivariadas de morfometria geométrica utilizando Relative Warps. Não foram encontradas diferenças significativas entre os indivíduos das populações analisadas de Schizolecis guntheri, sendo detectado apenas um dimorfismo sexual entre os exemplares pertencentes à Baía da Ilha Grande, no estado do Rio de Janeiro. Foi realizada uma revisão taxonômica, juntamente com a redescrição de gênero e espécie. Conforme resultados, conclui-se que todas as populações nas diversas bacias hidrográficas costeiras, de Santa Catarina ao Rio de Janeiro, são uma única espécie, Schizolecis guntheri.